ANALISIS USAHATANI PALA DI KAMPUNG TALAWID KECAMATAN KENDAHE KABUPATEN KEPULAUAN SANGIHE - Nolvi Sanggel; Olly E. H. Laoh; Grace A.J. Rumagit; Ellen G. Tangkere (COCOS, 2014)
ABSTRACTNolvi Sanggel. Analysis Nutmeg Farming in Talawid Village, Kendahe Sub District, Sangihe Islands Regency. Under the guidance O. Esry H. Laoh, as a Chairman, Grace A. J. Rumagit, and Ellen G. Tangkere as Members.The objective of this research is to analyze nutmeg farming in Talawid Village, Kendahe Sub District, Sangihe Islands Regency, Benefits of this research is to provide input and information materials for the development of nutmeg farming to related institution in order to increase their income.The method used in this study was "Purposive Sampling". Data used in this research is a primary data by using questionnaires that have been prepared are obtained from direct interviews with nutmeg farmers and secondary data from the Department of Agriculture, Livestock and Forestry and Village Office Talawid. Data obtained are presented in table form and then analyzed descriptively, followed by Return Cost Ratio analysis to determine the level of success of the farm.The results of this research showed that the average income Nutmeg farmers in the Village Talawid was Rp. 18,337,690, -. As costs incurred on average was Rp. 2,337,079, -. So that the average income received by farmers was Rp. 16,000,611, -. Analysis Results Return Cost Ratio (R/C) was 7.85, indicating that farming is done nutmeg experiencing gains.